OCHRONA KONSUMENTA NA PRZEŁOMIE EPOK – INSTYTUCJA RĘKOJMI W PRAWIE NAJNOWSZYM - Falkowska, Anna (Zeszyty Prawnicze, 2016)
CONSUMER PROTECTION AT THE TURN OF THE CENTURY –WARRANTY IN MODERN POLISH LAW Summary The presented article is devoted to development of warranty institution in the Polish modern law. The time frames of this article include the period between 1918 and 2003. The first date marks the beginning of the independent Polish country after the Second World War. The second date is connected with introducing in Poland a new law which implements the European Union directive. This new law concerns consumers and instead of a traditional warranty it introduces a new term of conformity with the contract.